Mundos del hispanismo una cartografía para el siglo XXI AIH Jerusalén 2019 - Fine, Ruth; Goldberg, Florinda F.; Hasson, Or (Iberoamericana Vervuert, 2022)
This volume collects works by Hispanists from different origins: from researchers whose mother tongue is Spanish and who carry out their work in the Hispanic world, whether peninsular or American, to those who work in regions where Spanish is a minority language and/or or who have acquired Spanish as a second language. This joyous diversity finds its expression in the works that make up this volume, highlighting one of the central objectives of the AIH: the academic and plural dialogue between the Hispanicisms of the world, an enriching and vivifying dialogue that knows no borders. Doing so for the first time outside of Europe and America takes on a very special significance, by inserting this multiplicity of perspectives into the present and much-needed dialogue between our peoples and regions. The printed book exclusively includes the opening speeches and plenary presentations, which were given by Myrna Solotorevsky, Patrizia Botta, Angela Schrott, Juan Diego Vila, Manuel Rivero Rodríguez and James Valender. The other papers are in open access